Risk management - Ramakrishna Reddy, K.; Murali Krishna, P. (New Delhi : Discovery, 2000)
In the Indian context; contributed articles.
Includes bibliographical references.
Keywords: Agricultural insurance -- India; Insurance -- India -- Management; Risk management -- India; Agriculture -- Economic aspects -- India